Aplikasi bakteriosin kasar berdasarkan nilai LC₅₀ untuk memperpanjang daya simpan udang putih: Aplikasi bakteriosin kasar berdasarkan nilai LC₅₀ untuk memperpanjang daya simpan udang putih - Sukmawati, Sukmawati; Metusalach, Metusalach; Syahrul, Syahrul (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Fishery products, including white shrimp, are highly perishable due to microbial contamination during postharvest handling. To address this, natural preservatives, such as bacteriocins, which are antimicrobial compounds produced by bacteria, including those from fermented shrimp paste, are being explored. This study aimed to evaluate the toxicity and preservative potential of three bacteriocin samples (TRS1, TRS2, and TRS3) using a 24-hour LC₅₀ test on Artemia sp. and antibacterial activity based on total plate count (TPC) in shrimp during storage. A completely randomized design (CRD) was used. Toxicity levels were assessed using probit analysis with log-linear regression to determine LC₅₀ values, and TPC was measured at 3-hour intervals over 24 h. Data were analyzed using the Kruskal-Wallis test and Dunn’s post-hoc test. TRS1 exhibited the highest toxicity, with an LC₅₀ of 0.22 µL/mL, followed by TRS3 (2.48 µL/mL) and TRS2 (4.40 µL/mL). Despite its higher toxicity, TRS1, along with TRS2, effectively suppressed microbial growth in shrimp, maintaining TPC values below the Indonesian National Standard (5×10⁵ CFU/g) throughout 24 h. In contrast, TRS3 maintained TPC below the threshold only up to 12 h, with counts nearing control levels (8.0×10⁶ CFU/g) by 24 h. TRS1 and TRS2 treatments initially showed fluctuating TPC patterns, followed by a sharp decline, possibly due to delayed bacteriocin activation and microbial adaptation; however, the exact reason remains unclear. Overall, TRS1 and TRS2 exhibited strong potential as natural preservatives for extending the shelf life of fresh white shrimp by effectively controlling bacterial growth during storage.